Adherence to the planetary health diet reduces dietary costs by 21% supporting affordable healthy eating among older adults in Iran - Maryam Karim Dehnavi; Hanieh Abbasi; Parisa Nezhad Hajian; Ahmadreza Dorosty Motlagh; Leila Azadbakht (Scientific Reports)
Abstract Poor dietary patterns among older adults are significantly influenced by socioeconomic status (SES) and food prices, impacting both diet quality and food choice. This study examines how dietary costs relate to the Planetary Health Diet Index (PHDI) and assesses the role of SES in Iran’s elderly population. In this cross-sectional study, 398 elderly individuals from southern Tehran were sampled. Dietary data were collected using a validated food frequency questionnaire, and adherence to the PHDI was evaluated based on EAT-Lancet guidelines. Food costs were derived from the Iranian Statistics Center and retail prices. Multivariable linear regression analyzed the relationship between PHDI adherence and dietary cost. PHDI adherence varied significantly across demographics. Higher adherence was observed in females (OR = 0.82, 95% CI: 0.71–0.95) and those with a BMI ≤ 27.5 (OR = 0.84, 95% CI: 0.73–0.97), while single individuals had higher scores (OR = 0.85, 95% CI: 0.74–0.98). Higher PHDI tertiles were linked to lower daily dietary cost, with a significant decrease observed in the highest tertile compared to the lowest (β = − 708,367 Rials, 95% CI: − 1,060,371 to − 356,362). However, this association was not significant among single and low-income participants. The study reveals that higher adherence to the PHDI is associated with reduced dietary costs, a key barrier to obtaining a healthy, balanced diet among older adults, and may thereby support better health outcomes, including malnutrition prevention and functional independence. Future research should focus on longitudinal studies to develop equitable public health strategies that promote affordable and sustainable dietary practices.